Magnetospheric contribution to low latitude Sq variation - Alex, S.; Rao, D.R.K. (My University, 1995)
Non-regular features noticed in the quiet-time diurnal variation of H component on 11 December,1990(Ap=2) and 12 December, 1990 (Ap = 7) in comparison with the average quiet day variations at a chain of equatorial, low and mid-latitude locations in the Indian longitude zone are studied. Stations away from the equatorial electrojet influence exhibited a minimum in the H field around 1600 LT followed by a secondary peak at 2100 LT. The globally observed anomalously enhanced variation in the "H" component at low and mid latitude is attributed to the effect of field aligned current driven by the magnetospheric plasma convection even during relatively quiet intervals. Causative mechanism to offset this peculiar feature, at equatorial locations is also discussed.
Keywords: Magnetospheric field; Low latitude; Sq variation; Equatorial electrojet